THEORETICAL STUDIES OF THE STRUCTURAL COMPATIBILITY OF THE MATERIALS OF THE OLD AND NEW CONCRETES DURING REPAIR OF TRANSPORT FACILITIES - Hromova, O. V. (Science and Transport Progress, 2006)
The article considers application of the finite-element analysis method of the ANSYS software for solution of tasks related to structural compatibility of the materials in the basis of a building structure – the old concrete and repair material vs. the new concrete with the purpose of theoretical substantiation of the coupling processes in repair of transport constructions.